The Relationship between Disease Activity Level and the Incidence of Depression in Systemic Lupus Erythematosus Patients at Haji Adam Malik Hospital Medan - Yohansen Martunas Sagala (Indonesian Journal of Rheumatology, 2025)
Background: Systemic Lupus Erythematosus (SLE) is a autoimmune disease that affects many organs of the body. SLE is a disease that cannot be completely cured. Life is difficult with SLE because the symptoms may come and go and it is unpredictable what will happen next. This condition causes the SLE patients feel unhappy, frustrated, angry, and sad. If this happens for a long time, it can cause SLE patients to experience depression. Methods: This study used a cross sectional design of 63 respondents at H. Adam Malik General Hospital Medan. This research data was obtained through history taking using primary data in the form of MEX SLEDAI questionnaires and Patient Health Questionnaire 9 (PHQ 9) and secondary data in the form of patient medical records. Results: It was found that SLE patients at H. Adam Malik General Hospital were all female, most of them were in the late adolescent age group with an age range of 17-25 years (39.7%), the last high school education level (68.3%), not working (81%), Married (54%), duration of SLE disease 1-2 years (36.5%), most SLE patients had mild disease activity levels (49.2%), most SLE patients have a mild depression (34,9%). There is a significant relationship between the level of disease activity and the incidence of depression in SLE patients at H. Adam Malik General Hospital (p ≤ 0.05) with a strong and unidirectional relationship (ρ = 0.64). Conclusion: There is a significant relationship between the level of disease activity and the incidence of depression in SLE patients at H. Adam Malik Hospital Medan with a strong relationship.